Transnational legal transplants and legitimacy: the example of 'clean' and 'green' development mechanisms. (2nd January 2018) - Penca, Jerneja
Abstract : The introduction of the Green Development Mechanism (GDM) as a governance tool for biodiversity conservation is presented as a legal transplant, originating in the Clean Development Mechanism from the climate regime. The case provides an instance of a transplanted legal idea not from one jurisdiction to another but between two transnational regimes. The legal transplantation approach highlights the motives for replication and factors that hinder it. In this context, the discussion reveals that while the GDM was constructed for effectiveness concerns, it was presented as a transplant in order to import to the newly established model legitimacy from the original one. Yet, a uniform acceptance of the transplant was prevented because of divergent evaluations of the original model. The existence of several, not one, ideologies and perceptions explains why transplanting is a highly unpredictable strategy for fostering acceptance of a legal idea in the transnational space, and ultimately for its implementation. Following the recognition that legitimacy cannot be inherited, the initiative employed a mixed strategy to ensure its acceptance, based on the democratic principles and effectiveness that are expected from non-state authorities, as well as the consensus-based, treaty-grounded 'rules of the game' of state actors. The case highlights how the universal endorsement of all states, and the appearance of alignment with international norms and intergovernmental institutions, remain significant goals of transnational initiatives.